2021
DOI: 10.1108/bfj-05-2021-0556
|View full text |Cite
|
Sign up to set email alerts
|

Food choice behavior: a case study in South Korea

Abstract: PurposeWith dining out increasing globally, policy making and research have been on menu labeling as a source for meaningful nutrition information. Yet, despite attempts to mandate menu labeling and the studies examining consumer's perception of menu nutritional information and how this perception impacts dining behavior and intention to consume, concerns for obesity and malnutrition continue to be at the forefront of public health discussions. This study attempts to comprehend consumers' nutritional goals, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
(121 reference statements)
0
2
0
1
Order By: Relevance
“…, 2001a, 2001b; Nayga 1996; Wang et al. , 1996; Kim et al 2022). Therefore, lower prices or cost incentives and nutritional education have been found to be effective strategies to encourage healthier food choices especially among low-income groups (French, 2003; Horgen and Brownell, 2002; Michels et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2001a, 2001b; Nayga 1996; Wang et al. , 1996; Kim et al 2022). Therefore, lower prices or cost incentives and nutritional education have been found to be effective strategies to encourage healthier food choices especially among low-income groups (French, 2003; Horgen and Brownell, 2002; Michels et al.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found price, taste, advertising/branding and convenience to be among the major contributing factors driving consumer food choices (Dana et al, 2021;French et al, 2001;Glanz et al, 1998;Plasek et al, 2020). The research shows that consumers with higher health knowledge/literacy socioeconomic status and healthier lifestyles and habits are more likely to use nutrition labels (Barreiro-Hurl e, et al, 2010;Kim, et al, 2001aKim, et al, , 2001bNayga 1996;Wang et al, 1996;Kim et al 2022). Therefore, lower prices or cost incentives and nutritional education have been found to be effective strategies to encourage healthier food choices especially among low-income groups (French, 2003;Horgen and Brownell, 2002;Michels et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Untuk itu perlu dilakukan penelitian lebih lanjut menggunakan variable lain seperti emosi, servicescape. nutritional information (Kim et al, 2022).…”
Section: Keterbatasan Dan Saranunclassified